Actuating the European Energy System Transition: Indicators for Translating Energy Systems Modelling Results into Policy-Making - Lehtveer, Mariliis; Göransson, Lisa; Heinisch, Verena; Johnsson, Filip; Karlsson, Ida; Nyholm, Emil; Odenberger, Mikael; Romanchenko, Dmytro; Rootzén, Johan; Savvidou, Georgia; Taljegard, Maria; Toktarova, Alla; et al. (Frontiers in Energy Research, 2021)
In this paper, we define indicators, with a focus on the electricity sector, that translate the results of energy systems modelling to quantitative entities that can facilitate assessments of the transitions required to meet stringent climate targets. Such indicators, which are often overlooked in model scenario presentations, can be applied to make the modelling results more accessible and are useful for managing the transition on the policy level, as well as for internal evaluations of modelling results. We propose a set of 13 indicators related to: i) the resource and material usages in modelled energy system designs; ii) the rates of transition from current to future energy systems; and iii) the energy security in energy system modelling results. To illustrate its value, the proposed set of indicators is applied to energy system scenarios derived from an electricity system investment model for Northern Europe. We show that the proposed indicators are useful for facilitating discussions, raising new questions, and relating the modelling results to Sustainable Development Goals and thus facilitate better policy processes. The indicators presented here should not be seen as a complete set, but rather as examples. Therefore, this paper represents a starting point and a call to other modellers to expand and refine the list of indicators.